Troubleshooting Multihop Wireless Networks - Qiu, Lili; Bahl, Paramvir; Rao, Ananth; Zhou, Lidong; Bahl, Victor (Microsoft Research, 2003)
Effective network troubleshooting is critical for maintaining efficient and reliable network operation. Troubleshooting is especially challenging in multi-hop wireless networks because the behavior of such networks depends on complicated interactions between many unpredictable factors such as RF noise, signal propagation, node interference, and traffic flows. In this paper we propose a new direction for research on fault diagnosis in wireless networks. Specifically, we present a diagnostic system that employs on-line trace-driven simulations to detect faults and perform root cause analysis. We apply this approach to diagnose performance problems caused by packet dropping, link congestion, external noise, and MAC misbehavior. In a 25 node multihop wireless network, we are able to diagnose over 10 simultaneous faults of multiple types with more than 80% coverage. Our framework is general enough for a wide variety of wireless and wired networks.